2020
DOI: 10.1097/md.0000000000023427
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pleiotropic effects of statins vs fibrates on laboratory parameters in patients with dyslipidemia

Abstract: Differences in the mechanism of action and potential pleiotropic effects between statins and fibrates would potentially drive a different effect on various laboratory parameters, but this remains controversial because of a paucity of reports comparing them. Therefore, the aim of this study was to compare the effects of statins and fibrates on laboratory parameters in Japanese patients in routine clinical practice. This retrospective cohort study included patients with dyslipidemia who had been newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Prescriptions are coded using the Japanese drug coding system, which is mapped to the Anatomical Therapeutic Chemical (ATC) classification. Several epidemiological studies have been previously published evaluating the effects of various drugs on laboratory parameters using NUSM’s CDW 17–20 . The experimental protocol was approved by the Ethical Committee of NUSM (approval number: P21‐01‐0), and the study was conducted in compliance with the Ethical Guidelines for Medical and Health Research Involving Human Subjects of the Ministry of Education, Culture, Sports, Science, and Technology and the Ministry of Health, Labour, and Welfare, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Prescriptions are coded using the Japanese drug coding system, which is mapped to the Anatomical Therapeutic Chemical (ATC) classification. Several epidemiological studies have been previously published evaluating the effects of various drugs on laboratory parameters using NUSM’s CDW 17–20 . The experimental protocol was approved by the Ethical Committee of NUSM (approval number: P21‐01‐0), and the study was conducted in compliance with the Ethical Guidelines for Medical and Health Research Involving Human Subjects of the Ministry of Education, Culture, Sports, Science, and Technology and the Ministry of Health, Labour, and Welfare, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, in a cohort of Japanese subjects who were LDL-cholesterol matched at baseline and were treated either with statins or fibrates, the overall mean LDL cholesterol level was lower by 27.3 mg/dl in statin users than in fibrate users ( P < 0.001) [ 49 ]. Furthermore, a meta-analysis of fourteen studies revealed that statin use significantly reduced VTE risk (OR, 0.81; 95% CI, 0.66–0.99, random-effect model), while the use of fibrates was associated with a significant increase in the risk of VTE (OR, 1.58; 95% CI, 1.23–2.02), and niacin did not change the risk of VTE [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrates, such as fenofi brate and gemfibrozil, are a group of lipid-lowering agents with the primary targets of lowering plasma TG and increasing HDL levels. 22,23 A Cochrane Review and metaanalysis examining six trials with a combined total of 16,135 individuals of all ages noted that, in comparison with patients on placebo, patients who underwent fi brate therapy saw a 16% reduction in risk for a combined outcome of CV death, non-fatal MI, or nonfatal stroke and a 21% reduction in the risk of a combined outcome of nonfatal MI or coronary heart disease death. 24 However, the Cochrane Review points out that "low-quality evidence suggests that fi brates have no eff ect on overall mortality or non-CVD mortality."…”
Section: Summary Of Pharmacologic Treatment Options For Dyslipidemia ...mentioning
confidence: 99%